MICROWAVE AND ULTRASONICATION ASSISTED EXTRACTION OF PHYTOCHEMICALS FROM B. monnieri AND STUDY OF ITS ANTIOXIDANT ACTIVITY - RENCY ELIZABETH THOMAS; S. D. KAMAT; D. V. KAMAT (International Journal of Pharma and Bio Sciences, 2014)
Plant extracts having an inhibitory effect on aging may be a good choice for cosmetic applications because of their natural origin. The extraction of bioactive compounds from plants is one of the most critical steps in the commercial development of natural products. Therefore rapid and efficient phytochemical extraction methods are essential. The present study involves the use of microwave and ultrasonication as methods to extract phytochemicals from B. monnieri. The efficiency of the extraction methods were studied by determining the saponin content and the antioxidant activity of the extracts by the Vanillin sulphuric acid and the DPPH method respectively. The study revealed a 5.01% increase in the yield of saponins and 12.61% increase in the antioxidant activity of the microwave extract. The extracts prepared using ultrasonication yielded a 1.47% and 9.08% increase in saponin content and antioxidant activity respectively. Thus the study revealed the superiority of Microwave and Ultrasonication assisted extraction compared to the conventional extraction method.